Occurrence, diel patterns, and the influence of melatonin on the photosynthetic performance of cultured Symbiodinium. Issue 1 (18th March 2013) - Roopin, Modi; Yacobi, Yosef Z.; Levy, Oren
Abstract: Dinoflagellata is the earliest phylum in which true circadian regulation of melatonin rhythms has been convincingly demonstrated. Here, diel profiling of melatonin in a cultured member of this phylum belonging to the genus Symbiodinium indicated that melatonin levels oscillate with significant nocturnal peaks. However, unlike in other previously studied dinoflagellate species, the diel rhythmicity of melatonin in Symbiodinium did not persist under constant dark conditions. Thus, the oscillating pattern of melatonin in Symbiodinium is presumed not to be driven by endogenous circadian control of melatonin production, but rather by changes in the daily photocycle, most likely through a mechanism involving the enhanced photo‐consumption of melatonin by free radicals. Although direct interactions of melatonin with detrimental radicals have been previously studied in several basal species, including dinoflagellates, none of these investigations addressed the effects that this molecule may have on photosynthesis, a major source of radical species in unicellular algae. In the present work, real‐time monitoring of oxygen evolution in Symbiodinium cultures indicated a significant decrease in photosynthesis rates upon treatment with various doses of melatonin. Analyses of chlorophyll a fluorescence and xanthophyll cycle activity confirmed this effect and further revealed that this slowdown may occur through an enhanced engagement of photoprotective mechanisms in melatonin‐treated cells. These findings are of great importance as they demonstrate that in certain photoautotroph species, the interactions of elevated melatonin levels with photosynthesis may extend beyond the general purpose of antioxidant protection.